Reconstruire les villes - Dogniez, Cécile; Capet, Emmanuelle; Gorea, Maria; Rouillard-Bonraisin, Hedwige; Massa, Francesco; Koch-Piettre, Renée (Brepols, 2019)
Le dixième anniversaire de la revue <span class=